Does crop diversification lead to climate-related resilience? Improving the theory through insights on practice - Vernooy, Ronnie (Informa UK Limited, 2022)
In recent years, CGIAR researchers have investigated the effectiveness of using agrobiodiversity, and more particularly crop and crop varietal diversity, as an adaptive practice to mitigate climate-change impacts on agriculture and to contribute to rural household and community resilience. The hypothesis informing this research is that the sustained practice of crop diversification leads to ecological redundancy, which allows farmer households and their communities to produce multiple positive livelihood benefits. The validity of this hypothesis is investigated by means of an extensive literature review (covering 2015–2020). Findings reveal ample evidence of positive outcomes, including increased yields and household incomes, improved nutrition and food security, new marketing opportunities, reduced poverty, and strengthened adaptive and innovative capacity. However, the evidence is far less convincing about the last part of the hypothetical impact pathway, i.e. the link between positive livelihood benefits and (increased) resilience. This shortcoming is addressed through the elaboration of a more clearly articulated theory of change for crop diversification and a refined methodology to support farmers in making appropriate diversification decisions. At the same time, the critical review opens a window on an important, novel perspective, which is to look at the role that crop diversification could play in a wider societal transition toward a more sustainable future.